Indoor positioning – an ad hoc positioning system - Mautz, Rainer (Geodesy and Cartography, 2012)
Th e aim of this paper is to discuss the development of an automatic, low-cost system that exploits current or near future wireless communications technology to enable continuous tracking the location of devices in all envi ronments. Th e development of such a wireless sensor network involves system design, digital signal processing, protocol development, extraction of ranges and localisation. Th is paper focuses on the user requirements, system architecture and network positioning. Th e user requirements are presented with a focus on applications in geodesy. A high level strategy for the positioning function is presented based on an ad-hoc geodetic network positioning method including issues of accuracy, quality and reliability of the node positions. Results show that it is possible to achieve a position deviation that is of the size of the ranging error.Padėties nustatymas patalposeSantrauka. Straipsnio tikslas – aptarti automatizuotos, pigios sistemos, taikančios jau esamas ar perspektyvias belaidžio ryšio technologijas prietaisų padėčiai sekti visose aplinkose. Tokio belaidžio jutiklių tinklo kūrimas susideda iš sistemos projektavimo, skaitmeninio signalo apdorojimo, protokolo parengimo, atstumų išskyrimo bei lokalizavimo. Straipsnyje aprašomi vartotojų reikalavimai, sistemos architektūra bei tinklo padėties nustatymas, daugiausia dėmesio skiriant sistemos paskirčiai geodezijoje. Aukšto lygio padėties nustatymo funkcijos strategija pateikta remiantis geodezinio tinklo padėties nustatymo metodu, atsižvelgiant į taško padėties nustatymo tikslumo, kokybės bei patikimumo poreikius. Iš tyrimų rezultatų akivaizdi galimybė, kad padėties nustatymo tikslumo nuokrypis būtų lygus atstumo nustatymo paklaidai.First published online: 03 Aug 2012